Measurement of neutron induced 86Sr(n, 2n)85Sr reaction cross sections at different neutron energies. (December 2019) - Shetty, Nidhi; Makwana, Rajnikant; Mehta, Mayur; Mukherjee, S.; Singh, N.L.; Suryanarayana, S.V.; Parashari, S.; Singh, R.; Naik, H.; Sharma, S.C.; Ayyala, S.; Soni, B.; et al.
Abstract: The cross-sections for 86 Sr (n, 2n) 85 Sr reaction are measured at neutron energies 19.44 ± 1.02 MeV and 16.81 ± 0.85 MeV wherein there is scarcity of data. The standard neutron activation analysis technique and offline gamma ray spectroscopy have been employed for measurement and analysis of the data. The results are compared with experimental data available in EXFOR database, JEFF-3.3, JENDL-4.0, TENDL-2017 and ENDF/B-VIII.0 evaluated data. The theoretical prediction was incorporated using nuclear modular codes TALYS 1.8 and EMPIRE 3.2.2. A detailed comparative study of experimental results with the theoretical models and various major evaluations has been presented.